Linkages and Trust in the Value Chain for Small‐scale Aquaculture in Asia. Issue 4 (6th March 2017) - Pomeroy, Robert; Navy, Hap; Ferrer, Alice Joan; Purnomo, Agus H.
Abstract: The small‐scale aquaculture (SSA) sector is recognized as making an important contribution to food security, poverty alleviation, and socioeconomic development. A value chain analysis can uncover insights into the linkages and trust within a value chain and constraints and challenges that face the sector. This paper examines the linkages and trust between SSA producers and traders in Asia in order to better understand the constraints and opportunities faced by small‐scale producers. The perspective revealed by the value chain analysis provides response strategies that can enhance the sustainability and competitiveness of the entire value chain and the actors that comprise it.